Tai Ji Quan: An overview of its history, health benefits, and cultural value - Yucheng Guo; Pixiang Qiu; Taoguang Liu (Elsevier, 2014)
Tai Ji Quan is considered to be a part of traditional Chinese Wushu (a martial art) and comprises various styles that have evolved historically from the Chen, Yang, Wǔ, Wú, and Sun families (schools). Recent simplification of the original classic styles has made Tai Ji Quan easier to adopt in practice. Thus, the traditional legacy of using Tai Ji Quan for self-defense, mindful nurturing of well-being, and fitness enhancement has been expanded to more contemporary applications that focus on promoting physical and mental health, enhancing general well-being, preventing chronic diseases, and being an effective clinical intervention for diverse medical conditions. As the impact of Tai Ji Quan on physical performance and health continues to grow, there is a need to better understand its historical impact and current status. This paper provides an overview of the evolution of Tai Ji Quan in China, its functional utility, and the scientific evidence of its health benefits, as well as how it has been a vehicle for enhancing cultural understanding and exchanging between East and West.